The colonial compromise: the threat of the gospel to the indigenous worldview - Tinker, George E.; De la Torre, Miguel A. (Lexington Books/Fortress Academic, 2021)
"This book explores the different types of compromises Indian people were forced to make and must continue to do so in order to be included in the colonizer's religion and culture. The contributors in this collection are in conversation with the contributions made by Tink Tinker"--